Organización y aplicación de material didáctico en talleres de lectura dentro del currículum de lengua y literatura para los niños y niñas de los segundos años de educación básica de la escuela " Pedro Vicente Maldonado " en el año 2012 - 2013. - Ugsha Coro, Manuel Aurelio (2013)
The present research was carried out in the public mixed school “Pedro Vicente Maldonado” in which all educational communities participated, then the purpose of the research was to design and apply didactic materials that promove interest towards reading and improve academic performance for children of second years of basic education during the years 2012 – 2013. So this proposal will help so much to improve their academic level as long as they are actively involved. The methods we have used are: The scientific method that let to check what we have researched, the historical method that allowed do the interpretation of possible results. Through the interview, survey and a detailed list we applied it was found that the reading problems exist because there is no motivation. In conclusion we known that it was necessary to talk more to teachers, because there was not stimulation for the development of knowledge in teaching correctly; while parents did not have a good communication with their children, the same who were not interested nor cared for learning because there was not prior motivation to the teaching so, this will serve them in their future professional career.